Pan-Asian adapted ESMO consensus guidelines for the management of patients with metastatic colorectal cancer: a JSMO–ESMO initiative endorsed by CSCO, KACO, MOS, SSO and TOS. (16th November 2017) - Yoshino, T; Arnold, D; Taniguchi, H; Pentheroudakis, G; Yamazaki, K; Xu, R -H; Kim, T W; Ismail, F; Tan, I B; Yeh, K -H; Grothey, A; Zhang, S; et al.
Abstract: The most recent version of the European Society for Medical Oncology (ESMO) consensus guidelines for the treatment of patients with metastatic colorectal cancer (mCRC) was published in 2016, identifying both a more strategic approach to the administration of the available systemic therapy choices, and a greater emphasis on the use of ablative techniques, including surgery. At the 2016 ESMO Asia Meeting, in December 2016, it was decided by both ESMO and the Japanese Society of Medical Oncology (JSMO) to convene a special guidelines meeting, endorsed by both ESMO and JSMO, immediately after the JSMO 2017 Annual Meeting. The aim was to adapt the ESMO consensus guidelines to take into account the ethnic differences relating to the toxicity as well as other aspects of certain systemic treatments in patients of Asian ethnicity. These guidelines represent the consensus opinions reached by experts in the treatment of patients with mCRC identified by the Presidents of the oncological societies of Japan (JSMO), China (Chinese Society of Clinical Oncology), Korea (Korean Association for Clinical Oncology), Malaysia (Malaysian Oncological Society), Singapore (Singapore Society of Oncology) and Taiwan (Taiwan Oncology Society). The voting was based on scientific evidence and was independent of both the current treatment practices and the drug availability and reimbursement situations in the individual participating Asian countries.